PECANANGAN PEMAYUN SEBAGAI KOMUNIKASI SIMBOLIK DALAM UPACARA PAWIWAHAN UMAT HINDU DI DESA SURANADI - Kariana, I Nengah Putra (IAHN Gde Pudja Mataram, 2025)
The Hindu wedding ceremony or pawiwahan is inseparable from the role of the spokesperson, known as pemayun and pecanangan. This research aims to explain the communication process and the symbolic meaning of the pemayun tools in the pawiwahan ritual. The research was conducted in Suranadi village, with the subject of the study being the pemayun figures, and the object of the study being the pecangan or canang bebaos, which function as a symbol of communication between the groom's and bride's parties. The research method is a qualitative descriptive method, where the research findings will be narrated in words. The research results show that the communication process is carried out through face-to-face interpersonal communication, involving both primary and secondary communication processes, with the use of symbols of pecanangan pemayun in the wedding ceremony as a medium of communication. The symbols and meanings of the tools used are as follows: betel leaves or base symbolize friendship, areca nuts reflect harmony in married life, lime symbolizes